Pygmalion in the archive: the mythic desires of colourisation. - Jolly, Martyn (Visual Studies, 2025)
In order to argue against the continued use of colourisation by our visual archives, I explore the desire for colour from the origins of photography onwards. I focus on the first desires for colour, which underpin all subsequent chromatic elaborations in both photography and film. Rather than dwelling on the metropolitan inventors of various colour processes, I look at some less well-known examples of colour in use by photographers and filmmakers associated with Australia and New Zealand. I argue that colourisation is another process within the continual entanglements of the 'monochromatic', the 'tinted', the 'toned', the 'painted' and the 'naturally coloured' which have defined the desire for colour from the beginning. Further, these original desires were realised differently in different places. Our archives should respect this richly variegated history and the capacity of their audiences to appreciate it, rather than being seduced by a mythic notion of a 'lifelike' image.